2022
DOI: 10.1109/access.2022.3182443
|View full text |Cite
|
Sign up to set email alerts
|

Novel Compact UWB Planar Monopole Antenna Using a Ribbon-Shaped Slot

Abstract: Ultra-Wideband (UWB) is a wireless communication technology that can be utilized for precise indoor positioning system. UWB is low power-consuming and resistant to complex multipath environments, thanks to a short pulse signal. Since the main desired characteristics of the UWB antennas for radio-frequency localization systems are wide bandwidth, omnidirectional radiation pattern, and low profile for simple integration with printed circuit boards, various planar monopole antennas for UWB applications were propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…It is understood from Table 5 that the proposed antenna is smaller in size (length × width) than the antennas in literature 7,8,12,13,18,29,40,50 and lesser in thickness than 5,7,9,11,13,17,18,29,34,38,40 . This lesser thickness of the antenna results in reduced overall volume.…”
Section: Transient Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…It is understood from Table 5 that the proposed antenna is smaller in size (length × width) than the antennas in literature 7,8,12,13,18,29,40,50 and lesser in thickness than 5,7,9,11,13,17,18,29,34,38,40 . This lesser thickness of the antenna results in reduced overall volume.…”
Section: Transient Analysismentioning
confidence: 90%
“…But the SAR of the antenna is very close to the health limits. In Park and Jung, 12 an UWB antenna with ribbon‐shaped slot is introduced for achieving UWB bandwidth. It has a reasonable peak gain with omnidirectional radiation characteristics only.…”
Section: Introductionmentioning
confidence: 99%
“…It is also preferred in portable and body-worn scenarios due to getting less detuned in proximity to lossy media such as the human body [4], [5]. Some examples of very recent compact UWB studies fed by MS, CPW (grounded CPW) and ACS can be found in [6], [7], [8], and [9], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the UWB (Ultra-Wideband) monopole antenna attainment of larger bandwidth with a miniaturized structure is a challenging one. In literature UWB (Ultra-Wideband) performance is obtained by availing some structural changes in the patch like a U-shaped slot paired with a rectangular microstrip line (Mishra et al , 2011), a circular and semi-circular slot (Ahmed and Sebak, 2008) with a microstrip line, a C-shaped resonator (Ahmed et al , 2022), and a ribbon-shaped slot (Park and Jung et al , 2022). Due to re-radiation, the usage of a microstrip feed line produces radiations at higher frequencies resulting in electromagnetic interference among the circuits.…”
Section: Introductionmentioning
confidence: 99%